Richard Wagner’s Der Ring des Nibelungen: Medieval, Pagan, Modern - Cusack, Carole M. (Relegere, 2013)
Richard Wagner’s Der Ring des Nibelungen is a Romantic work that draws on medieval narrative and thematic elements (e.g., the Poetic Edda, the Völsunga Saga, and the Nibelungenlied). Wagner’s cycle is a polyvalent work of art and can be interpreted as exemplifying both secularisation, as the gods of Valhalla give way to humanity, and reenchantment, in that its performance allows the gods of Germanic myth to “live” on stage. This article addresses the issue of reception by looking at Wagner’s medievalism, the modern Heathenry movement and its use of the Pagan past as a source of legitimation, and finally by examining attendance of performances of the Ring as a significant secular ritual activity that engages with Pagan gods and brings them to modern audiences, Heathen and otherwise.